MOTIVATIONAL FACTORS INFLUENCING INDONESIAN STUDENTS IN UNDERTAKING A MASTER’S DEGREE - Sumit Choemue; Concilianus Laos Mbato (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
Education is one of the necessities for cultivating people and the country. It cannot be separated from human life since it is considered as a life-long learning process without limitation. Students have different reasons, factors, and motivations to study a Master’s Degree. This study aimed at investigating motivational factors that impact Indonesian students to undertake a Master’s Degree in English Education. Mixed methods research design was employed to identify and understand the specific information focusing on students’ motivation. The data were collected through questionnaires and in-depth interviews. Graduate students studying in the first semester of the English Education Master’s Program at Sanata Dharma University, Yogyakarta, participated in this study. The obtained data were analyzed using descriptive statistics and displayed in the mean score and the level of motivation. The findings indicated that, in general, students were intrinsically motivated in embarking on their Master’s Degree (m=3.99), with a high level of intrinsic motivation. The data from the interviews revealed that at least three motivational factors were influencing students in pursuing a Master’s Degree, namely personal, environmental, and profession-oriented factors. This study provides suggestions for future research.